2022
DOI: 10.3389/fphar.2022.1007719
|View full text |Cite
|
Sign up to set email alerts
|

Administration of recombinant human thrombopoietin is associated with alleviated thrombocytopenia in adult intensive care unit patients with pneumonia: A single-center retrospective study

Abstract: Background: Recombinant human thrombopoietin (rhTPO) is reported to stimulate platelet production and increase peripheral platelet counts; it is primarily used to manage chemotherapy-induced thrombocytopenia and idiopathic thrombocytopenic purpura. However, the effect of rhTPO in patients with pneumonia and thrombocytopenia remains uncertain.Objective: To assess the association of rhTPO and platelet counts in ICU patients with pneumonia and thrombocytopenia.Materials and Methods: A retrospective cohort study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Currently, rhTPO is widely used in clinical thrombocytopenia as an HGF drug, and its radiation protection potential is gradually being explored [ 25 ]. Additionally, several studies demonstrated it brought significant improvements in acute radiation sickness [ 22 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, rhTPO is widely used in clinical thrombocytopenia as an HGF drug, and its radiation protection potential is gradually being explored [ 25 ]. Additionally, several studies demonstrated it brought significant improvements in acute radiation sickness [ 22 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%